PERBANDINGAN PENDAPATAN DAN LABA ATAU RUGI TERHADAP PRESTASI KLUB DAN TINGKAT KEKOMPETITIFAN ENGLISH PREMIER LEAGUE (Studi Kasus pada Tujuh Klub English Premier League) - Josua Paimatua Hizkia; Endang Kiswara (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to analyze the factors that affect the sporting performance and the competitiveness level of English Premier League. The examined factors of this research are clubs revenue and clubs profit or loss in a year as the key benchmark.The populations in this study are seven clubs which participated in English Premier League in the period of 2014-2016. The samples are Manchester United FC, Manchester City FC, Chelsea FC, Arsenal FC, Tottenham Hotspur FC, Everton FC, and Leicester City FC. The data that was used in this research was secondary data and selected by using documentation method. Model analysis using comparative qualitative analysis.The analysis of this research showed that the rate of club income and its profit or loss are not the differentiator of a club sporting performance nor English Premier League competitiveness rate.